Unexpected formation of [5]helicenes from hexaarylbenzenes containing pyrrole moieties. Issue 5 (13th April 2017) - Ammon, Felix; Sauer, Stephanie Theresia; Lippert, Rainer; Lungerich, Dominik; Reger, David; Hampel, Frank; Jux, Norbert
Abstract : Surprisingly helical: a pyrrolic [5]helicene embedded into a six-membered ring framework is preferred over a heterocyclic pendant of hexabenzocoronene. Abstract : A synthetic route to hexaarylbenzenes containing up to six pyrrole units was developed. These pyrrole moieties are connected to the central benzene core via their β-carbon atom. Oxidative cyclodehydrogenation of systems containing one pyrrole ring led to the formation of [5]helicenes instead of the completely fused coronene-like structure.